Early and efficient pregnancy diagnosis in ewes: expression profile of ISG15 mRNA in peripheral blood leucocytes compared to transrectal ultrasonography - KIYMA, Z; KOSE, M; KAYA, M S; ATLI, M O (The Indian Journal of Animal Sciences, 2017)
The objective of this study was to compare the measurement of one of interferon-tau stimulated genes (ISGs; ISG15) expression in peripheral blood leukocytes (PBLs) with transrectal ultrasonography (TUSG) for early pregnancy detection in ewes. Ewes (46) were examined 18 and 25 days after mating by TUSG. PBL samples were collected from 16 pregnant ewes on the day of mating (d0) and on days 15 and 18 after mating. Total RNAs were extracted from PBLs and converted to cDNA. ISG15 mRNA expression was detected using qPCR in triplicate. All pregnancies were confirmed by birth. In TUSG examinations on day 18, the embryonic vesicle and embryonic vesicle plus the embryo were visible for 14 and 32 ewes, respectively, of the 46 total. Both the embryonic vesicle and embryo were detected in 42 ewes on day 25. Four ewes out of 46 with a visible embryonic vesicle on day 18 were detected as non-pregnant on day 25. While significant differences in ISG15 mRNA expression levels of PBLs were detected in 13 of 16 ewes on day 15, ISG15 mRNA levels for all ewes were significantly different on day 18, compared with levels on the day of mating. The results suggested that profiles of ISG15 mRNA can provide pregnancy detection earlier than TUSG.